An update on prophylactic human papillomavirus (HPV) vaccines - Šterbenc, Anja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2019)
Prophylactic human papillomavirus (HPV) vaccines have revolutionarily modified our understanding of and efforts in preventing communicable diseases. Undeniably, all three prophylactic HPV vaccines currently available have excellent safety and have substantially contributed to the control of HPV infections and HPV-related diseases during the past decade in the setting where high vaccine coverage has been achieved. This review summarizes and discusses the most influential peer-reviewed literature on HPV vaccines published between September 2018 and September 2019. The review focuses on the current status of HPV vaccination implementation, results from recent clinical trials, updates to recommendations and guidelines, long-term immunogenicity, and evaluations of various dosing schemes and HPV vaccination of alternative populations. In addition, we briefly summarize studies on the real-life effectiveness of prophylactic HPV vaccines from countries with successful HPV vaccination programs, present an update on safety data, and discuss progress and the development of novel prophylactic HPV vaccines, as well as potential future applications and challenges.
Keywords: human papillomavirus; humani papiloma virus; literature review; pregled literature; profilaktična cepiva proti HPV; prophylactic HPV vaccines